MANAJEMEN TAHFIDZ MELALUI PROGRAM MAJELISAN UNTUK MENINGKATKAN MUTU HAFALAN SANTRI DI PPIQ PONDOK PESANTREN NURUL JADID - Abdurrahman Abdurrahman; Muhammad Iqbal (STKIP Pesisir Selatan, 2026)
This study aims to examine the implementation of the majelisan program in improving the quality of Quran memorization among students at Nurul Jadid Islamic Boarding School in the Zaid bin Tsabit region. This study employs a qualitative approach using field research methods. Data collection techniques included observation, interviews, and documentation, with the research subjects being the Quran memorization instructors and students participating in the majelisan program. The results indicate that the Majelis program is implemented through structured stages of planning, execution, and evaluation of Quranic memorization. The program involves reciting memorized portions from memory (bil ghaib) for surahs in multiples of five without any days off, and is exclusively open to students who have already memorized at least five surahs or multiples thereof. The majelisan program is able to improve the quality of students’ memorization through discipline, reinforcement of murajaah, and responsibility in maintaining their Quranic memorization. Thus, the majelisan program is considered effective as a strategy for improving the quality of students’ memorization. Its novelty lies in the research subjects and approach, which focus on the majelis program. The majelis program has distinctive characteristics, including collective memorization training, a disciplined review process, intensive supervision, tiered evaluation, which have not been extensively studied in research on Islamic education management, particularly in the context of Qur’anic memorization.